2018
DOI: 10.1016/j.jhin.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-C decontamination of hand-held tablet devices in the healthcare environment using the Codonics D6000™ disinfection system

Abstract: Mobile phones and tablet computers may be contaminated with micro-organisms and become a potential reservoir for cross-transmission of pathogens between healthcare workers and patients. There is no generally accepted guidance on how to reduce contamination on mobile devices in healthcare settings. Our aim was to determine the efficacy of the Codonics D6000™ UV-C disinfection device. Daily disinfection reduced contamination on screens and on protective cases (test) significantly, but not all cases (control) cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Even though bacterial loads get below the detection limit directly after disinfection by UV-C, recontamination via hands and other -often contaminated-hospital environments occurs relatively quickly, returning to pre-disinfection levels within 48 hours. 9 These studies suggest that a daily or twice daily disinfecting round with UV-C should result in a consistent low bacterial load. Upon implementation, placement of the UV-Smart D25 should be considered carefully.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even though bacterial loads get below the detection limit directly after disinfection by UV-C, recontamination via hands and other -often contaminated-hospital environments occurs relatively quickly, returning to pre-disinfection levels within 48 hours. 9 These studies suggest that a daily or twice daily disinfecting round with UV-C should result in a consistent low bacterial load. Upon implementation, placement of the UV-Smart D25 should be considered carefully.…”
Section: Discussionmentioning
confidence: 91%
“…The post UV-C reduction in bacterial load was to be expected, since the effectivity of UV-C light for disinfecting smartphones and tablets has been shown to be more effective than other sanitization methods. 6,9 Others also found (almost) complete reductions in bacterial loads in cycles of 35-60 seconds, whereas Huffman et al stated that no bacterial growth was observed after having inoculated inactive phones and ID-badges for 48 hours with known amounts of bacteria and subsequent disinfection. 5,9…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet light is an alternative to chemical agents for disinfecting surfaces, but does not solve the issue of increased cleaning rates nor is it completely absolved from health implications [ 51 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of disinfection methods [1] Efficiency of disinfection methods [2], [5] Efficiency of automated UV methods to disinfect spaces [3], [4], [7], [8], [10], [11], [12], [28], [32], [35], [49], [50] Effectiveness of non-automated UV methods for disinfecting spaces [15], [16], [17], [18], [20], [22], [23], [27] Ineffectiveness of UV methods to disinfect spaces [26], [45] Effectiveness of UV methods for disinfecting devices [6], [14], [25], [31], [41], [42], [43] Susceptibility of Covid 19 to UV methods [29], [30] Insufficient evidence of susceptibility of Covid 19 to UV methods [46] Covid prevention methods 19 [34] Reduction of costs in the manufacture of UV equipment [9] Detecting the level of UV light in public spaces [13], [21], [37], [51] Development and detection of UV energy sources [38], [39], [40], [44]<...>…”
Section: Temas Y Funcionalidad Referencesmentioning
confidence: 99%
“…[15], [16], [17], [18], [20], [22], [23], [27] They evaluated the cleaning time with the dose of UVC light for the disinfection of nosocomial materials and bacteria [6], [14], [25], [31], [41], [42], [43] They used intelligent devices for UV monitoring and prediction in public areas, while evaluating efficiency at the time of disinfection. [13], [21], [37], [51] Remote UVC light sources are used in public environments is safe and economical to reduce environmentally transmitted diseases.…”
Section: Temas Y Funcionalidad Referencesmentioning
confidence: 99%